2020
DOI: 10.1017/s0033291720002056
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain-oscillatory and ex-Gaussian markers of remission and persistence of ADHD

Abstract: Abstract Background Attention-deficit/hyperactivity disorder (ADHD) often persists into adolescence and adulthood, but the processes underlying persistence and remission remain poorly understood. We previously found that reaction time variability and event-related potentials of preparation-vigilance processes were impaired in ADHD persisters and represented markers of remission, as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Adults with ADHD also showed greater variability of stimulus processing (i.e., weaker theta phase consistency) than controls during MW in the MWT (with a similar pattern not reaching statistical significance in the SAT), but not during task focus. As such, decreased neural efficiency in ADHD may be specific to MW periods, consistent with a link between theta phase consistency and attentional impairments in individuals with ADHD ( Vainieri et al, 2020 ). Compared to controls, adults with ADHD also showed significantly weaker beta increases during task focus in the MWT, but no differences during MW nor task focus in the SAT, consistent with the group differences in response execution during the more challenging MWT identified in Analysis 1.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Adults with ADHD also showed greater variability of stimulus processing (i.e., weaker theta phase consistency) than controls during MW in the MWT (with a similar pattern not reaching statistical significance in the SAT), but not during task focus. As such, decreased neural efficiency in ADHD may be specific to MW periods, consistent with a link between theta phase consistency and attentional impairments in individuals with ADHD ( Vainieri et al, 2020 ). Compared to controls, adults with ADHD also showed significantly weaker beta increases during task focus in the MWT, but no differences during MW nor task focus in the SAT, consistent with the group differences in response execution during the more challenging MWT identified in Analysis 1.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, studies on ADHD samples have reported reduced event-related theta increase and phase consistency during cognitive tasks ( Groom et al, 2010 , Michelini et al, 2018 , Juurmaa et al, 2020 , Khoshnoud et al, 2018 , Michelini et al, 2022 ). Of note, these alterations in theta activity were recently linked to task increased variability in reaction times and developmental persistence of ADHD into adulthood ( Vainieri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although different methodological approaches were used, the findings of studies in adults revealed increased RT variability in adults with MDD (Gallagher et al, 2015;Kaiser et al, 2008;Vallesi et al, 2015;van den Bosch et al, 1996). While this pattern resembles the increase in intra-individual RT variability observed in patients with ADHD (Karalunas et al, 2014;Pievsky and McGrath, 2018;Vainieri et al, 2020), it cannot be ruled out that this overlap was due to ADHD-related impairments given that this comorbidity was not taken into account in the adult samples. In contrast, intra-individual RT variability was not impaired in a sample of adolescents and young adults with MDD with no co-morbid ADHD and the same patients did not show any alterations in intra-individual RT variability when assessed during childhood before they had developed MDD (Roy et al, 2017).…”
Section: Current Depressionmentioning
confidence: 77%
“…All other identified meta-analyses did not report on this domain. Because intra-individual RT variability is central to ADHD (Karalunas et al, 2014;Pievsky and McGrath, 2018;Vainieri et al, 2020), we performed an additional literature search on individual studies assessing intra-indivdual RT variability from neurocognitive tasks on" cold" cognitive functions in MDD revealing four cross-sectional and two longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has also reported contrasting findings between MRT and mu, where individuals with ADHD exhibited slower MRT and faster mu (Gu et al, 2013;Hervey et al, 2006;Hwang-Gu et al, 2019). Yet other studies have reported no group differences in mu, using a range of tasks including the N-back, flanker, oddball, and both simple and complex Go No-Go tasks (Feige et al, 2013;Seymour et al, 2016;Vainieri et al, 2009Vainieri et al, , 2022. The SART is very simple and highly predictable, leading to an increase in boredom.…”
Section: Discussionmentioning
confidence: 99%